Antioxidant effects of the orientin and vitexin in Trollius chinensis Bunge in D-galactose-aged mice★ - An, Fang (Medknow Publications & Media Pvt Ltd, 2012)
Total flavonoids are the main pharmaceutical components of Trollius chinensis Bunge, and orientin and vitexin are the monomer components of total flavonoids in Trollius chinensis Bunge. In this study, an aged mouse model was established through intraperitoneal injection of D-galactose for 8 weeks, followed by treatment with 40, 20, or 10 mg/kg orientin, vitexin, or a positive control (vitamin E) via intragastric administration for an additional 8 weeks. Orientin, vitexin, and vitamin E improved the general medical status of the aging mice and significantly increased their brain weights. They also produced an obvious rise in total antioxidant capacity, superoxide dismutase, catalase, and glutathione peroxidase levels in the serum, and the levels of superoxide dismutase, catalase and glutathione peroxidase, Na(+)-K(+)-ATP enzyme, and Ca(2+)-Mg(2+)-ATP enzyme in the liver, brain and kidneys. In addition, they significantly reduced malondialdehyde levels in the liver, brain and kidney and lipofuscin levels in the brain. They also significantly improved the neuronal ultrastructure. The 40 mg/kg dose of orientin and vitexin had the same antioxidant capacity as vitamin E. These experimental findings indicate that orientin and vitexin engender anti-aging effects through their antioxidant capacities.